2013
DOI: 10.1155/2013/657849
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Elimination of Perfluorinated Compounds Using Cholestyramine and Chlorella pyrenoidosa

Abstract: Background. While perfluorinated compounds (PFCs) are a family of commonly used synthetic compounds with many applications, some PFCs remain persistent within the human body due, in part, to enterohepatic recirculation and renal tubular reabsorption. With increasing recognition of potential harm to human health associated with PFC bioaccumulation, interventions to facilitate elimination of these toxicants are welcome in order to potentially preclude or overcome illness. Minimal research has been undertaken thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Medication use was checked, and no one reported usage of cholestyramine [a medication that influences PFAS elimination ( Genuis et al. 2010 , 2013 )], therefore, medication use was not included in the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication use was checked, and no one reported usage of cholestyramine [a medication that influences PFAS elimination ( Genuis et al. 2010 , 2013 )], therefore, medication use was not included in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Working task, duration of employment, number of glasses of water per day, blood donation, and pregnancy before mitigation of PFAS exposure from drinking water can influence the initial serum levels but would not be expected to influence the PFAS half-life. Medication use was checked, and no one reported usage of cholestyramine [a medication that influences PFAS elimination (Genuis et al 2010(Genuis et al , 2013], therefore, medication use was not included in the model. C70.97 (0.28-1.9) 1.6 (0.49-6.2) <LOD (<LOD-0.16) L-PFOS (C8) 6.5 (5.4-13) 11 (5.5-28) 3.0 (0.30-9.8) 1m-PFOS (C8) 0.52 (0.25-2.7) 1.0 (0.32-4.1) 0.18 (<LOD-0.59) 3/4/5m-PFOS C82.9 (1.2-6.7) 4.9 (1.7-17) 0.79 (0.10-2.2) 2/6m-PFOS C81.8 (0.84-3.2) 2.6 (1.0-7.5) 0.46 (<LOD-1.4)…”
Section: Modeling Of Pfas Elimination and Estimating Of Half-lifementioning
confidence: 99%
“…For example, it is currently uncertain if human elimination of 1m-PFOS (e.g. urine (Zhang et al, 2013a)) or feces (Genuis et al, 2013) is enantioselective. In rats, there was no evidence for enantioselective urinary elimination or tissue distribution (Wang et al, 2011b), but species differences could exist.…”
Section: Temporal Trends Of 1m-pfos Efmentioning
confidence: 99%
“…Recent studies have shown that PFHxS is a substrate for NTCP in both human and rat hepatocytes 44,45 . A case study involving eight subjects has found that oral treatment with BAs sequestrant increased fecal elimination of PFHxS 46 . Although no human study supporting the paraben-BAs association was found, in vitro studies have observed that paraben acts as a strong obesogenic compound through PPAR-activation at high concentrations (high  range) in murine 3T3-L1 cells 47,48 .…”
Section: Based On the Correlations Between Pfhxs And Bas In Ffmentioning
confidence: 99%